Gsm teletraffic engineering measurement for traffic type / Khairul Parman Zakaria - Zakaria, Khairul Parman (1997)
The objective of this thesis is to collect and tabulate data of traffic type to control and to monitor the performance of Global System for Mobile Communication (GSM) telephone network. The data presented shows an overview of the traffic flow in an exchange. Traffic measurement are used primarily to check the service performance, to monitor the system capacity and to determine the grade of service (GOS) that the customer are receiving. The aim of traffic measurement is to enable the administration to manage and plan network effectively and efficiently. This paper explains how to measure the GSM telephone traffic and how to analyze the measured traffic data. Traffic data is collected only for basic traffic type which is defined by the origin and the destination. From the data, daily analysis is made and graphs are plotled. From this observation, the traffic measurement on exchange and surrounding telephone network will provide the data and traffic flow is monitored. Relatively simple program has been written in C++ computer Ianguage for system capacity planning-radio channel to the final solution for radio channel that is used for forecast and dimensioning for future requirements. The capacity planning is very useful to determine how many circuits are equired on a given route in order to control the proportion of blocked calls. From this observation, further recommendations are made wïth other considerations in order to provide the best performance for the customers.